Catalytic and Structural Characterization of a Browning-Related Protein in Oriental Sweet Melon (Cucumis Melo var. Makuwa Makino) - Liu, Siyu; Murtaza, Ayesha; Liu, Yan; Hu, Wanfeng; Xu, Xiaoyun; Pan, Siyi (Frontiers in Chemistry, 2018)
Polyphenol oxidase (PPO) in plants plays an important role in browning reactions and may affect the quality of sweet melon products. In this study, a browning-related protein (BRP) with PPO activity was partially purified from oriental sweet melon (Cucumis melo var. makuwa Makino) by salt precipitation and column chromatography. The BRP possessed a high degree of identity with several chitinase proteins, particularly defense-related proteins, by MS identification. Pyrogallol was determined as the most appropriate substrate for BRP (Km = 0.04278 M). BRP exhibited extreme resistance under alkaline and high temperature conditions when pyrogallol was used as substrate. Electrophoresis analysis indicated that BRP was a homo-dimer of two subunits and had a molecular weight of 37 kDa. Structural analysis indicated that the α-helix was the dominant conformation of BRP. The active site of the protein might be buried deeply in the protein, and BRP might be monodispersed in an aqueous system.